Assessment of Land Capability for Urban Building Height Planning in Bukittinggi, Indonesia - Mulia, Fajar Agung; Handayani, Wiwandari (Universitas Islam Sultan Agung Semarang, 2024)
With urban development and rapid growth, the challenge of land capability to accommodate urbanization is becoming increasingly complex. Therefore, the concept of a